Revolutionizing Optical Wireless Communications via Smart Optics - Amr M. Abdelhady; Osama Amin; Mohamed-Slim Alouini; Basem Shihada (IEEE Open Journal of the Communications Society, 2022)
The heterogeneity of optical wireless networks (OWNs) has expanded over decades in terms of services, node densities, mobility requirements, bandwidth needs, responsiveness, and physical device profile. Consequently, incorporating dynamic reconfigurability into future OWNs can satisfy their diverse realm of objectives. Towards this end, we provide our vision for the potential gains of integrating tunable optical elements in OWNs reflected in energy consumption reduction, coverage customization, data transfer rate boosting, highly accommodating multiple access schemes, enhancing physical layer security, supporting simultaneous services, and interference reduction. Finally, we speculate a roadmap for future research directions in tunable optics aided OWNs and the associated challenges with their deployment and operation.